Preparation method of UNS N08825 alloy electroslag cast ingot

By adopting the five-member slag system and the optimized smelting process, the problem of uneven burning of Ti elements during electroslag remelting is solved, which significantly improves the composition uniformity and surface quality of the electroslag ingot and improves the yield rate.

CN119913361APending Publication Date: 2025-05-02XIAN JUNENG SUPERALLOY MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411989609.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The prior art causes uneven burning of Ti elements during electroslag remelting, affecting the composition uniformity and corrosion resistance of the alloy. The surface quality of the prepared electroslag ingots is poor, the slag skin is thick, and the content of Al and Ti at the head and tail is obvious.

Method used

The five-membered slag system (CaF2, CaO, Al2O3, TiO2, MgO) is used to remelter electroslag. By optimizing the melting process parameters and slag composition ratio, the melting speed and slag pendulum are controlled, and the refining temperature and time are refined to ensure the uniform distribution of Ti and Al elements.

Benefits of technology

The surface quality of the electroslag ingot is achieved, the slag skin is thin and uniform, and the distribution of Al and Ti elements at the head and tail is very small, which improves the composition uniformity and yield rate of the ingot.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913361A_ABST
    Figure CN119913361A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a UNS N08825 alloy electroslag cast ingot. The preparation method comprises the following steps that S1, burdening is conducted according to UNS N08825 alloy components, wherein the UNS N08825 alloy components comprise, by weight, smaller than or equal to 0.02% of C, 21.0-23.5% of Cr, 40-43% of Ni, smaller than or equal to 0.2% of Al, 0.9-1.2% of Ti, 3.0-3.5% of Mo, 2.0-3.0% of Cu, smaller than or equal to 0.5% of Si, smaller than or equal to 1.0% of Mn, smaller than or equal to 0.01% of S, smaller than or equal to 0.01% of P and the balance Fe; the preparation method comprises the following steps: weighing metal Fe, a graphite block, a Ni plate, a FeMo intermediate alloy, a FeCr intermediate alloy, metal Cr, a Ti block, Al beans, a pure Cu tube and electrolytic Mn according to the weight percentage; the invention provides a novel five-membered slag system formula which comprises 250-58% of CaF, 12-16% of CaO, 12-16% of Al2O3, 7-9% of TiO2 and 4-6% of MgO, after the slag system is used for electroslag remelting, the surface quality of an electroslag ingot can be improved, the burning loss of the Ti element is remarkably reduced, and the component uniformity of the cast ingot is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-temperature alloy smelting, and in particular to a method for preparing a UNS N08825 alloy electroslag ingot. Background Art

[0002] UNS N08825 (NS1402) alloy is a solid solution strengthened Fe-Ni-Cr based corrosion resistant alloy, which is widely used in the fields of petroleum, chemical industry, nuclear power, aerospace, etc. Whether a vacuum induction furnace (VIM), an electric furnace (EAF) or a non-vacuum induction furnace (AIM) is used as the initial smelting process, the final smelting process is usually electroslag remelting (ESR). Due to the oxidation and burning of the easily oxidizable element Ti at the slag-gold interface during the electroslag remelting process, the Ti distribution in the axial direction of the electroslag ingot is uneven. Ti is an important alloying element in nickel-based corrosion resistant alloys, which directly affects the microstructure, mechanics and corrosion resistance of the alloy. In order to control and improve the uniformity of alloy composition and reduce the burning of Ti elements, optimizing the slag composition ratio is one of the important ways.

[0003] At present, the alloy is usually smelted by a ternary slag system (CaF2, CaO, Al2O3) or by adding TiO2 powder to it. The electroslag ingots prepared by this method still have problems such as poor surface quality, thick slag skin, and obvious differences in Al and Ti content between the head and tail of the ingot. This will lead to a decrease in the subsequent yield and obvious differences in the performance of forged rods at the head and tail. Summary of the invention

[0004] In view of the above problems, the present invention provides a method for preparing N08825 alloy electroslag ingots. The present invention develops a five-element slag system. By using the slag system to smelt UNS N08825 alloy, an electroslag ingot with good surface quality, thin and uniform slag skin, and small extreme difference of aluminum and titanium elements at the head and tail can be obtained, thereby achieving the purpose of improving the uniformity of ingot composition and increasing the yield.

[0005] In order to achieve the above object, the technical solution adopted by the present invention comprises the following steps:

[0006] S1: According to the UNS N08825 alloy composition, the weight percentage is: C≤0.02%, Cr: 21.0-23.5%, Ni: 40-43%, Al≤0.2%, Ti: 0.9-1.2%, Mo: 3.0-3.5%, Cu: 2.0-3.0%, Si≤0.5%, Mn≤1.0%, S≤0.01%, P≤0.01%, Fe: balance. According to the above weight percentage, weigh metal Fe, graphite block, Ni plate, FeMo master alloy, FeCr master alloy, metal Cr, Ti block, Al bean, pure Cu tube, electrolytic Mn.

[0007] S2: Melting in a vacuum induction furnace: Place the preheated ingot mold into the ingot mold chamber and then cast to obtain an electroslag electrode.

[0008] S3: electroslag electrode surface grinding treatment;

[0009] S4: Protective atmosphere electroslag remelting: The prepared electroslag electrodes are welded, centered, loaded into the furnace and evacuated. After argon is filled to 1.2 bar, the process parameters are input for smelting. The melting rate and slag swing are controlled during the smelting process. After the smelting is completed, it is cooled for a certain period of time and taken out of the furnace to obtain the electroslag ingot.

[0010] Preferably, the order of adding elements in step S2 is: (Ni, Fe, Cr, Mo, C)→(Ti, Al, Cu)→Mn.

[0011] Preferably, refining begins after all Ni, Fe, Cr, Mo, and C materials are melted, the refining temperature is 1460-1500° C., the refining time is 60±10 min, the vacuum degree of the furnace during the refining period is less than 0.2 Pa, and stirring is turned on during the refining period. The O content of the molten steel before adding Ti and Al is 50-70 ppm, and the N content is 80-100 ppm.

[0012] Preferably, a five-component slag system is used in step S4, and the weight percentages of the five-component slag system are: CaF2 50-58%, CaO 12-16%, Al2O3 12-16%, TiO2 7-9%, and MgO 4-6%.

[0013] Preferably, the electrode size used in the electroslag remelting in step S4 is Φ410-450 mm, the diameter of the crystallizer is Φ530-550 mm, the slag amount is 80-110 kg, and the melting rate is 200-300 kg / h.

[0014] Preferably, the slag addition ratio before power is supplied to the electroslag remelting is 20-30%, and the remaining slag material is added 5-10 minutes after power is supplied, and the addition of the remaining slag material is completed within 30 minutes.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The invention develops a five-element slag system. By using the slag system to smelt UNS N08825 alloy, an electroslag ingot with good surface quality, thin and uniform slag skin, and small difference in aluminum and titanium elements at the head and tail can be obtained, thereby achieving the purpose of improving the uniformity of ingot composition and increasing the yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a diagram of an electroslag ingot according to Example 1 of the present invention;

[0018] Figure 2This is the key parameter curve of electroslag smelting in Example 1 of the present invention;

[0019] Figure 3 This is a diagram of the electroslag ingot of Comparative Example 1 of the present invention;

[0020] Figure 4 This is the key parameter curve of electroslag smelting in comparative example 1 of the present invention. DETAILED DESCRIPTION

[0021] The present application is further described in detail below with reference to the accompanying drawings and examples. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] The present invention provides a method for preparing N08825 alloy electroslag ingot, and the specific scheme is as follows:

[0023] S1: According to the UNS N08825 alloy composition, the weight percentage is: C≤0.02%, Cr: 21.0-23.5%, Ni: 40-43%, Al≤0.2%, Ti: 0.9-1.2%, Mo: 3.0-3.5%, Cu: 2.0-3.0%, Si≤0.5%, Mn≤1.0%, S≤0.01%, P≤0.01%, Fe: balance. According to the above weight percentage, weigh metal Fe, graphite block, Ni plate, FeMo master alloy, FeCr master alloy, metal Cr, Ti block, Al bean, pure Cu tube, electrolytic Mn.

[0024] S2: Melting in a vacuum induction furnace. Put the preheated ingot mold into the ingot mold chamber and then cast to obtain the electroslag electrode.

[0025] S3: Surface grinding of electroslag electrode.

[0026] S4: Protective atmosphere electroslag remelting: The prepared electroslag electrodes are welded, centered, loaded into the furnace and evacuated. After argon is filled to 1.2 bar, the process parameters are input for smelting. The melting rate and slag swing are controlled during the smelting process. After the smelting is completed, it is cooled for a certain period of time and taken out of the furnace to obtain the electroslag ingot.

[0027] Furthermore, the mass percentages of some elements in step S1 are as follows: C 0.009-0.012%, Ti: 1.1-1.2%, Cu 2.5-2.8%.

[0028] Furthermore, the order of adding elements in step S2 is: (Ni, Fe, Cr, Mo, C)→(Ti, Al, Cu)→Mn.

[0029] Further, after all the Ni, Fe, Cr, Mo, and C materials are melted, refining begins, the refining temperature is 1460-1500°C, the refining time is 60±10min, the vacuum degree of the furnace during the refining period is <0.2Pa, and stirring is turned on during the refining period. Before adding Ti and Al: the temperature of the molten steel is controlled at 1460-1480°C, the O content is 50-70ppm, and the N content is 80-100ppm.

[0030] Furthermore, in step S2, the pouring temperature is 1480°C to 1510°C, and the ingot mold preheating temperature is 400°C.

[0031] Furthermore, in step S4, the weight percentages of the five-component slag system are: CaF2 50-58%, CaO 12-16%, Al2O3 12-16%, TiO2 7-9%, and MgO 4-6%.

[0032] Furthermore, in step S4, the electrode size used in electroslag remelting is Φ410-450 mm, the diameter of the crystallizer is Φ530-550 mm, the slag amount is 80-110 kg, and the melting rate is 200-300 kg / h.

[0033] Furthermore, the slag addition ratio before power is supplied to the electroslag remelting is 20-30%, and the remaining slag material is added 5-10 minutes after power is supplied, and the addition of the remaining slag material is completed within 30 minutes.

[0034] The present invention is further described in detail below with reference to specific embodiments and comparative examples.

[0035] Example 1

[0036] UNS N08825 electroslag ingots were prepared as follows:

[0037] (1) Vacuum induction melting: The high-temperature alloy raw materials are melted in an 8-ton vacuum induction furnace. The chemical composition of the alloy is:

[0038]

[0039]

[0040] VIM furnace vacuum degree <5Pa, leakage rate <25mbar / L·s -1Then add Ni plate, Fe block, metal Cr, Mo bar, graphite block in turn, heat up until melted and then start refining. The refining temperature is 1465℃, the refining time is 60min, the vacuum degree of the furnace chamber during the refining period is <0.1Pa, and stirring is turned on during the whole refining period. Before adding Ti and Al, the temperature of the molten steel and the gas content of the sample in front of the furnace are tested. Ti, Al and Cu are added when the temperature of the molten steel is 1463℃, the O content is 61ppm, and the N content is 85ppm. Before adding Mn sheets, fill Ar to 100hPa, and after adding Mn sheets, electromagnetic stirring is performed for 10min before pouring.

[0041] The temperature of the molten steel was adjusted to 1508°C and ready for pouring. The ingot mold with a preheated temperature of 400°C was hung in the ingot mold room for pouring, and after vacuum cooling in the ingot mold room for 120±5min, it was taken out of the furnace and demolded to obtain the induction casting ingot.

[0042] The surface of the induction ingot is polished until no oxide scale is visible to obtain the electroslag electrode.

[0043] After the electroslag electrode and auxiliary electrode are welded, the furnace is loaded, aligned, and evacuated and filled with argon, electroslag smelting is carried out. The pre-melted slag ratio is: CaF257.0%, CaO 15.2%, Al2O314.4%, TiO28.1%, MgO 6.0%, and the rest are impurities such as SiO2, FeO, and MnO. The copper crystallizer specification is Φ540mm. The amount of slag added is 120kg.

[0044] Electroslag smelting is divided into three stages: slag melting stage, stabilization stage and shrinkage feeding stage. Melting speed-slag swing control is adopted in the stabilization stage.

[0045] Process parameters in the slag-melting stage: power: 320kW→530kW→500kW→450kW→360kW; slag resistance: 4.1mohm→5.8mohm→5.4mohm→5.0mohm→4.3mohm; time: 1min→10min→20min→30min→40min.

[0046] Process parameters in the stable stage: melting rate 290kg / h, slag swing 0.36mohm.

[0047] Process parameters of the feeding stage: power: 100% → 80% → 60% → 45% → 30%, time: 1min → 15min → 35min → 45min → 60min. The starting weight of the feeding is 200kg, and the ending weight of the feeding is 20kg. After the feeding is completed, the power is turned off, and the electroslag ingot is taken out of the furnace after cooling for 120min.

[0048] Figure 1The electroslag ingot prepared in this embodiment has good surface quality, a thin and uniform slag skin, no surface defects such as steel penetration points and slag grooves, and can be directly forged without peeling, which significantly improves the yield and production efficiency. Figure 2 These are the key parameters of electroslag smelting in this embodiment. It can be seen that the smelting process is stable and the melting rate is controllable.

[0049] After the head and tail of the electroslag ingot are cut off normally, the components are tested as shown in the following table:

[0050] Element / wt% Ni Cr Mo Fe Al C Si Mn Ti Cu head 42.11 22.85 3.22 Remain 0.11 0.010 0.21 0.09 1.12 2.52 Tail 42.10 22.87 3.22 Remain 0.12 0.010 0.20 0.09 1.08 2.50

[0051] From the table above, we can see that the ingot composition is uniform, and the deviation of Al and Ti composition at the head and tail is small. Compared with the electrode composition, no obvious phenomenon of "increasing Al and burning Ti" is observed.

[0052] Comparative Example 1

[0053] (1) Vacuum induction melting: The high-temperature alloy raw materials are melted in an 8-ton vacuum induction furnace. The chemical composition of the alloy is:

[0054] Element / wt% Ni Cr Mo Fe Al C Si Mn Ti Cu UNSN08825 42.25 22.83 3.12 Remain 0.15 0.012 0.20 0.09 1.14 2.49

[0055] VIM furnace vacuum degree <5Pa, leakage rate <25mbar / L·s -1 Then add Ni plate, Fe block, metal Cr, Mo bar, graphite block in turn, heat up until melted and then start refining. The refining temperature is 1468℃, and the refining time is 60min. Before adding Ti and Al, the temperature of the molten steel and the gas content of the sample in front of the furnace are tested. When the temperature of the molten steel is 1461℃, the O content is 65ppm, and the N content is 75ppm, Ti, Al, and Cu are added. Before adding Mn sheets, fill Ar to 100hPa, and after adding Mn sheets, electromagnetic stirring is performed for 10min before pouring.

[0056] The temperature of the molten steel was adjusted to 1505°C and ready for pouring. The ingot mold with a preheated temperature of 400°C was hung in the ingot mold room for pouring, and after vacuum cooling in the ingot mold room for 120±5min, it was taken out of the furnace and demolded to obtain the induction casting ingot.

[0057] The surface of the induction ingot is polished until no oxide scale is visible to obtain the electroslag electrode.

[0058] After the electroslag electrode and the auxiliary electrode are welded, the furnace is loaded, the center is aligned, and the vacuum is filled with argon, the electroslag smelting is carried out. Comparative Example 1 uses a quaternary slag system, and the pre-melted slag ratio is: CaF262.4%, CaO 16.2%, Al2O316.4%, TiO24.4%, and the rest are impurities such as MgO, SiO2, FeO, and MnO. The copper crystallizer specification is Φ540mm. The amount of slag added is 120kg.

[0059] Electroslag smelting is divided into three stages: slag melting stage, stabilization stage and shrinkage feeding stage. Melting speed-slag swing control is adopted in the stabilization stage.

[0060] Process parameters in the slag-melting stage: power: 320kW→530kW→500kW→450kW→360kW; slag resistance: 4.1mohm→5.8mohm→5.4mohm→5.0mohm→4.3mohm; time: 1min→10min→20min→30min→40min.

[0061] Process parameters in the stable stage: melting rate 290kg / h, slag swing 0.36mohm.

[0062] Process parameters of the feeding stage: power: 100% → 80% → 60% → 45% → 30%, time: 1min → 15min → 35min → 45min → 60min. The starting weight of the feeding is 200kg, and the ending weight of the feeding is 20kg. After the feeding is completed, the power is turned off, and the electroslag ingot is taken out of the furnace after cooling for 120min.

[0063] Figure 3 The electroslag ingot prepared in Comparative Example 1 shows that the surface quality of the electroslag ingot is poor, the slag skin is thick, and there are multiple surface defects such as steel penetration points and slag grooves. The surface needs to be treated before forging to prevent cracking or folding. Figure 4 These are the key parameters of electroslag smelting in comparative example 1. It can be seen that the smelting process is unstable and abnormalities such as melting rate fluctuations occur.

[0064] After the head and tail of the electroslag ingot are cut off normally, the components are tested as shown in the following table:

[0065] Element / wt% Ni Cr Mo Fe Al C Si Mn Ti Cu head 42.24 22.82 3.11 Remain 0.17 0.012 0.21 0.09 1.11 2.48 Tail 42.25 22.84 3.11 Remain 0.20 0.012 0.20 0.09 0.92 2.49

[0066] From the table above, it can be seen that the ingot composition uniformity is poor. Compared with Example 1, the deviation of the Al and Ti components at the head and tail increases. Compared with the electrode composition, an obvious "increasing Al and burning Ti" phenomenon occurs. In particular, the Ti element is burned to 0.92%, which is close to the lower limit of 0.90%.

[0067] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing UNS N08825 alloy electroslag ingot, characterized in that: The following steps are involved: S1: Prepare materials according to the UNS N08825 alloy composition: weight percentage: C≤0.02%, Cr: 21.0-23.5%, Ni: 40-43%, Al≤0.2%, Ti: 0.9-1.2%, Mo: 3.0-3.5%, Cu: 2.0-3.0%, Si≤0.5%, Mn≤1.0%, S≤0.01%, P≤0.01%, Fe: balance; weigh metal Fe, graphite block, Ni plate, FeMo master alloy, FeCr master alloy, metal Cr, Ti block, Al bean, pure Cu tube, electrolytic Mn according to the above weight percentage; S2: Melting in a vacuum induction furnace: placing the preheated ingot mold into the ingot mold chamber and then casting to obtain an electroslag electrode; S3: electroslag electrode surface grinding treatment; S4: Protective atmosphere electroslag remelting: The prepared electroslag electrodes are welded, aligned, loaded into the furnace and vacuumed, and after argon is filled to 1.2 bar, the process parameters are input for smelting; the melting rate and slag swing are controlled during the smelting process, and after the smelting is completed, the electroslag ingot is cooled for a certain period of time and taken out of the furnace to obtain; The S4 adopts a five-component slag system, and the weight percentages of the five-component slag system are: CaF2 50-58%, CaO 12-16%, Al2O3 12-16%, TiO2 7-9%, and MgO 4-6%.

2. The method for preparing a UNS N08825 alloy electroslag ingot according to claim 1, characterized in that: The order of adding elements in S2 is: (Ni, Fe, Cr, Mo, C)→(Ti, Al, Cu)→Mn.

3. The method for preparing a UNS N08825 alloy electroslag ingot according to claim 2, characterized in that: After all Ni, Fe, Cr, Mo and C materials are melted, refining begins. The refining temperature is 1460-1500°C, the refining time is 60±10min, the vacuum degree of the furnace chamber during the refining period is <0.2Pa, stirring is turned on during the whole refining period, and the O content of the molten steel before adding Ti and Al is 50-70ppm, and the N content is 80-100ppm.

4. The method for preparing a UNS N08825 alloy electroslag ingot according to claim 1, characterized in that: The electrode size used in the electroslag remelting in S4 is Φ410-450mm, the crystallizer diameter is Φ530-550mm, the slag amount is 80-110kg, and the melting rate is 200-300kg / h.

5. The method for preparing a UNS N08825 alloy electroslag ingot according to claim 1, characterized in that: The slag addition ratio of the electroslag remelting before power supply is 20-30%, and the remaining slag material is added 5-10 minutes after power supply, and the addition of the remaining slag material is completed within 30 minutes.